2004 IEEE 35th Annual Power Electronics Specialists Conference (IEEE Cat. No.04CH37551)
DOI: 10.1109/pesc.2004.1355739
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic control for m-parallel connected DC-DC buck converters

Abstract: Absfracf-A promising new approach, synergetic control theory, based on ideas of self-organization, is used to design control for the general case of m parallel-connected DC-DC buck converters serving resistive load. A general nonlinear synergetic PI control algorithms are derived using averaged models of the system. Using the general control laws, two particular cases are considered. They are two and three parallel-connected DC-DC buck converter systems. It is shown that the derived controls suppress unmeasure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 7 publications
(1 reference statement)
0
24
0
1
Order By: Relevance
“…(8) and (9) into Eq. (24) and rearranging, the synergetic control law is then obtained, which is given by:…”
Section: Design Of Power System Stabilizer Using Synergetic Control Tmentioning
confidence: 99%
See 1 more Smart Citation
“…(8) and (9) into Eq. (24) and rearranging, the synergetic control law is then obtained, which is given by:…”
Section: Design Of Power System Stabilizer Using Synergetic Control Tmentioning
confidence: 99%
“…Recently, this theory has been successfully applied in the area of power electronics controls. For instance, its application to a single boost converter was introduced in [21], and some practical aspects with reference to both simulations and actual hardware were discussed in [22][23][24]. Also, synergetic control theory was satisfactorily applied in a practical battery charging system [25].…”
Section: Introductionmentioning
confidence: 99%
“…The synergetic control was developed by Kolesnikov et al [20] on the basis of the standard variable structure control. The method was later applied to a number of industrial processes, including problems in energy conversion [21][22][23][24][25]. In [24], the authors presented the optimization characteristic of the synergetic control method and showed that the control law can be derived using the analytical design of aggregated regulators (ADAR) method and calculus of variation principles.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the problem of control design for paralleled buck converters has been addressed by such advanced techniques as sliding control [7], feedback linearization control [9], fuzzy logic control [10], and synergetic control [11,12,13,14]. Almost all these approaches are focused on equal current sharing among system converters and do not consider system level optimization of the system behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all these approaches are focused on equal current sharing among system converters and do not consider system level optimization of the system behavior. In contrast, the results presented in [12,14] have addressed the problem of dynamic current sharing by introducing this capability of synergetic control on the basis of a two-buck converter system feeding resistive load and constant power load respectively.…”
Section: Introductionmentioning
confidence: 99%